Elastoplastic Deformation and Fracture Behavior of Cr-Coated Zr-4 Alloys for Accident Tolerant Fuel Claddings - Ma, Xianfeng; Zhang, Wenjie; Chen, Zejia; Yang, Dong; Jiang, Jishen; Song, Ligang; Tu, Jiajun; Zhai, Hailin (Frontiers in Energy Research, 2021)
In-situ tensile tests and crystal plasticity finite element modeling (CPFEM) were used to study the deformation and cracking behaviors of Cr-coated Zr-4 alloys for accident tolerant fuel claddings under tension. Based on the experimental results, vertical cracks in the coating generally initiated from the interface between the coating and the substrate, and expanded to the top surface of the coating. In addition, under large deformation, the vertical cracks also resulted in interfacial cracks that initiated from the cracking tips and propagated along the interface. According to the CPFEM, the cracking behaviors were mainly caused by the substantial stress concentration at the coating/substrate interface and at the grain boundaries in the Cr coating. The preferential crack initiation was related to the strain localization associated with grain orientation variation and strain mismatch.